Dissociation of putative graft-versus-haematopoiesis and graft-versus-myeloma effects in patients with rapidly progressive multiple myeloma* - Luft, Thomas; Moos, Marion; Goldschmidt, Hartmut; Ho, Anthony Dick; Görner, Martin (British journal of haematology, 2003)
Summary. This study evaluates the immunological effects in 21 patients with multiple myeloma (MM) following allogeneic stem cell transplantation with a non-myeloablative conditioning regimen. Patients were heavily pretreated, most of them having progressed despite one to three courses of high dose chemotherapy followed by autologous stem cell rescue. For patients conditioned with low dose total body irradiation and Fludarabine, development of full (100%) donor chimerism (FDC) within the first 3-4 months strongly depended on the number of T cells transplanted. This putative graft-versus-haematopoiesis effect, however, did not coincide with clinical response. Rather, 10 of 17 patients progressed although FDC in peripheral blood was achieved. In contrast, clinical graft-versus-host disease (GvHD) of grade III-IV was associated with disease remission. Four of six patients achieved complete remission (CR) and one patient achieved a partial remission (PR) in close temporal relation with their acute GvHD. Two of four patients in CR succumbed to the consequences of this side effect. One patient in PR progressed soon after successful treatment of the GvHD, one of two patients with a long-lasting CR developed chronic GvHD. Our observations suggest the existence of two distinct immune effects in MM following allogeneic transplantations with reduced conditioning regimen. First, the putative graft-versus-haematopoiesis effect that induced FDC was observed in all patients receiving unmanipulated grafts. Secondly, the graft-versus-myeloma effect that induced CR did not correlate with FDC but was associated with grade III-IV GvHD in our group of heavily pretreated patients.